Style Analysis of Keçecizade İzzet Molla's Qasida Titled "Nu'ût-ı Risâlet ve Âl-i Resûl" - Soylu, İlhan (Taner NAMLI, 2025)
Keçecizade İzzet Molla, who lived in 19th century, is one of the last master poets of Divan Literature with his verse and prose Works. In this century-long poetry tradition, qasida and eulogy are the poets' essential verse form. The naat, which is based on inspiration and expresses heartfelt and sincere feelings with a lyrical expression, is one of the most common and admired genres of Divan poetry. In this article, İzzet Molla's 50 couplet naat, which is located at the very beginning of his Divan and begins with a direct eulogy to the Prophet, will be evaluated in terms of style. Firstly, paraphrasing of the qasida will be done then its linguistic, phonetic and morphological features will be analyzed, then its content, parts and literary/aesthetic aspects will be emphasized.

19. yüzyılda yaşayan Keçecizade İzzet Molla, manzum ve mensur eserleriyle Divan şiirinin son usta şairlerinden biridir. Asırlar süren bu şiir geleneğinde kaside ve naat, şairlerin vazgeçilmez nazım şekli ve türleri arasında yer alır. İlham kaynaklı olup içten ve samimi duyguların lirik bir anlatımla dile getirildiği naat, Divan şiirinin en yaygın ve beğenilen türlerindendir. Bu makalede, İzzet Molla’nın Divan’ının hemen başında yer alan ve doğrudan Hz. Peygamber’e methiyeyle başlayan 50 beyitlik naatı, üslup yönünden değerlendirilecektir. İlk olarak kasidenin dil içi çevirisi yapılacak sonra dil, ses ve şekil özellikleri incelenecek, akabinde muhtevası, bölümleri ve edebî/estetik yönü üzerinde durulacaktır.
Keçecizade İzzet Molla’nın Nu‘ût-ı Risâlet ve Âl-İ Resûl Başlıklı Kasidesinin Üslup İncelemesi
Keywords: Communication and Media Studies (Other); İletişim ve Medya Çalışmaları (Diğer)